The microRNA miR-34a inhibits non-small cell lung cancer (NSCLC) growth and the CD44hi stem-like NSCLC cells. - Yang Shi; Can Liu; Xin Liu; Dean G Tang; Junchen Wang (PLoS ONE, 2014)
Lung cancer is among the most lethal malignancies with a high metastasis and recurrence rate, which is probably due to the existence of lung cancer stem cells (CSCs). CSCs in many tumors including non-small cell lung cancer (NSCLC) have been identified using adhesion molecular CD44, either individually or in combination with other marker(s). MicroRNAs (miRNAs) regulate both normal stem cells and CSCs and dysregulation of miRNAs has been implicated in tumorigenesis. Recently, miR-34a was found to be downregulated in NSCLC cells but the biological functions of miR-34a in regulating NSCLC cell behavior have not been extensively studied. Here we show that transfection of synthetic miR-34a, but not the negative control (NC) miRNA oligonucleotides (oligos) in three NSCLC cell lines, i.e., A549, H460, and H1299, inhibited their holoclone formation, clonogenic expansion, and tumor regeneration in vivo. Furthermore, the lentiviral vector-mediated overexpression of miR-34a in purified CD44hi H460 cells also inhibited tumor outgrowth. In contrast, expression of miR-34a antagomirs (i.e., antisense oligos) in the CD44lo H460 cells promoted tumor development. Our study shows that miR-34a is a negative regulator of the tumorigenic properties of NSCLC cells and CD44hi lung CSCs, and establishes a strong rationale for developing miR-34a as a novel therapeutic agent against NSCLC.